2004
DOI: 10.1083/jcb.200312123
|View full text |Cite
|
Sign up to set email alerts
|

Kazrin, a novel periplakin-interacting protein associated with desmosomes and the keratinocyte plasma membrane

Abstract: Periplakin forms part of the scaffold onto which the epidermal cornified envelope is assembled. The NH2-terminal 133 amino acids mediate association with the plasma membrane and bind a novel protein, kazrin. Kazrin is highly conserved and lacks homology to any known protein. There are four alternatively spliced transcripts, encoding three proteins with different NH2 termini. Kazrin is expressed in all layers of stratified squamous epithelia; it becomes membrane associated in the suprabasal layers, coincident w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 14 publications
4
107
0
Order By: Relevance
“…The Western blot also revealed a faint doublet, suggesting that kaz A and possibly B were present; however, because of the low amount of protein from 125 eggs, it was difficult to consistently resolve the doublet of kaz A and B. Of interest, the Western blot revealed a band at the correct molecular weight for kaz C. Previously, only kaz A and B transcripts had been identified in mice (Groot et al, 2004). To further confirm our Western results, we subjected eggs to RT-PCR using primers to each kaz A-D as well as primers that recognize all isoforms.…”
Section: Kazrin In Mouse Eggsmentioning
confidence: 90%
See 4 more Smart Citations
“…The Western blot also revealed a faint doublet, suggesting that kaz A and possibly B were present; however, because of the low amount of protein from 125 eggs, it was difficult to consistently resolve the doublet of kaz A and B. Of interest, the Western blot revealed a band at the correct molecular weight for kaz C. Previously, only kaz A and B transcripts had been identified in mice (Groot et al, 2004). To further confirm our Western results, we subjected eggs to RT-PCR using primers to each kaz A-D as well as primers that recognize all isoforms.…”
Section: Kazrin In Mouse Eggsmentioning
confidence: 90%
“…Recently, convincing evidence revealed a novel noncanonical plakin interacting protein, kazrin (kaz), which acts as a cytolinker protein linking periplakin to the plasma membrane in keratinocytes (Groot et al, 2004). Of interest, images in Groot et al (2004) showed evidence that kaz brings desmosomal plakins such as periplakin and desmoplakin (DP) into close proximity with actin filaments near adherens junctions implying that kaz may act as a cytolinker functionally connecting adherens junctions and desmosomes (Groot et al, 2004).…”
Section: Fig 1 Kaz Colocalizes To the Spindle Apparatusmentioning
confidence: 99%
See 3 more Smart Citations